Crystal Structures of Two Isozymes of Citrate Synthase from Sulfolobus tokodaii Strain 7 - Midori Murakami; Tsutomu Kouyama (Biochemistry Research International)
Thermoacidophilic archaeon Sulfolobus tokodaii strain 7 has two citrate synthase genes (ST1805-CS and ST0587-CS) in the genome with 45% sequence identity. Because they exhibit similar optimal temperatures of catalytic activity and thermal inactivation profiles, we performed structural comparisons between these isozymes to elucidate adaptation mechanisms to high temperatures in thermophilic CSs. The crystal structures of ST1805-CS and ST0587-CS were determined at 2.0 Å and 2.7 Å resolutions, respectively. Structural comparison reveals that both of them are dimeric enzymes composed of two identical subunits, and these dimeric structures are quite similar to those of citrate synthases from archaea and eubacteria. ST0587-CS has, however, 55 ion pairs within whole dimer structure, while having only 36 in ST1805-CS. Although the number and distributions of ion pairs are distinct from each other, intersubunit ion pairs between two domains of each isozyme are identical especially in interterminal region. Because the location and number of ion pairs are in a trend with other CSs from thermophilic microorganisms, the factors responsible for thermal adaptation of ST-CS isozymes are characterized by ion pairs in interterminal region.